Building Brand Loyalty Through Trust: The Impact of Social Media Marketing and Service Quality at Toko Kopi Tuku - Adawiyah, Indah; Churiyah, Madziatul; Dhewi, Titis Shinta (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the role of brand trust in mediating the influence of social media marketing and service quality on brand loyalty in Toko Kopi Tuku consumers. A total of 225 respondents were selected using purposive sampling technique, with the criteria that individuals follow the @tokokopituku Instagram account and have made purchases more than twice in the last six months. Data was collected using a likert scale questionnaire with a range of 1 (strongly disagree) to 5 (strongly agree). The analysis was conducted using the SEM-PLS (Partial Least Squares) method to test the proposed structural model. The results showed that social media marketing has no significant effect on brand loyalty, while service quality has a significant effect. In addition, both social media marketing and service quality have a significant effect on brand trust, and brand trust has a significant effect on brand loyalty. Furthermore, brand trust is able to mediate the relationship between social media marketing and service quality on brand loyalty. These results highlight the importance of building consumer trust as a bridge in optimizing digital marketing strategies and service quality to increase brand loyalty.